SPL-108 mitigates metastasis and chemoresistance in tubo-ovarian carcinoma - Olivia D. Lara; Elke Van Oudenhove; Luiza Pereira; Selim Misirlioglu; Douglas A. Levine; Kari E. Hacker (Translational Oncology)
Background: Overcoming the heterogeneous mechanisms of metastasis and chemoresistance will improve outcomes for women with tubo-ovarian carcinomas (TOCs). CD44 expression has been shown to be associated with poor prognosis and advanced disease in TOCs. In addition, studies have shown a link between chemoresistance and CD44 pathways. Given the therapeutic implications of targeting CD44, this manuscript examines the biologic effects of a novel CD44 modulator, SPL-108, in TOCs. Materials and Methods: We assessed the effects of SPL-108 on chemosensitivity and migration in a panel of ovarian cancer cell lines with varied CD44 and MDR1 expression. In vitro experiments (cell viability assay, Western blot analysis, Calcein AM fluorescence assay, and migration assay) were carried out to determine the functional effects of SPL-108 in TOCs. Findings: Ovarian cancer cell lines OVCAR5 and OVCAR8 expressed higher protein levels of CD44 as demonstrated through Western Blot analysis. SPL-108 treatment significantly decreased the number of migrating cells in OVCAR8, OVCAR5 and OVCAR3 cell lines and migratory response was independent of CD44 expression. Treatment with SPL-108 led to significant accumulation of the MDR1 substrate Calcein in OVCAR5, OVCAR8 and OVCAR3 cells lines compared to verapamil treated positive control cells. Retention of Calcein after SPL-108 treatment was seen in cell lines with high MDR1 protein expression and no Calcein retention was seen in cells lacking MDR1 expression, suggesting SPL-108 inhibits MDR1. Conclusions: SPL-108 treatment has anti-metastatic properties and may play a role in chemoresistance in preclinical models of TOCs independent of CD44 expression. Ongoing in vitro and in vivo studies will help guide further clinical development of SPL-108.